Dexmedetomidine alleviates host ADHD-like behaviors by reshaping the gut microbiota and reducing gut-brain inflammation. (May 2023) - Xu, Xiangzhao; Zhuo, Lixia; Zhang, Linjuan; Peng, Huan; Lyu, Yixuan; Sun, Huan; Zhai, Yifang; Luo, Danlei; Wang, Xiaodan; Li, Xinyang; Li, Liya; Zhang, Ying; et al.
Highlights: DEX alleviates ADHD-like behaviors and corrects aberrant EEG rhythms. DEX reshapes the gut microbiota and promotes the enrichment of beneficial bacteria. DEX ameliorates intestinal and cerebral inflammation in SHRs. Gut microbiota transfer recapitulates DEX-mediated therapeutic effects in SHRs. Abstract: Attention-deficit/hyperactivity disorder (ADHD) is one of the most prevalent psychiatric disorders that affects children and even continues into adulthood. Dexmedetomidine (DEX), a short-term sedative, can selectively activate the α2-adrenoceptor. Treatment with α2-adrenergic agonists in patients with ADHD is becoming increasingly common. However, the therapeutic potential of DEX for the treatment of ADHD is unknown. Here, we evaluated the effect of DEX on ADHD-like behavior in spontaneously hypertensive rats (SHRs), a widely used animal model of ADHD. DEX treatment ameliorated hyperactivity and spatial working memory deficits and normalized θ electroencephalogram (EEG) rhythms in SHRs. We also found that DEX treatment altered the gut microbiota composition and promoted the enrichment of beneficial gut bacterial genera associated with anti-inflammatory effects in SHRs. The gut pathological scores and permeability and the level of inflammation observed in the gut and brain were remarkably improved after DEX administration. Moreover, transplantation of fecal microbiota from DEX-treated SHRs produced effects that mimicked the therapeutic effects of DEX administration. Therefore, DEX is a promising treatment for ADHD that functions by reshaping the composition of the gut microbiota and reducing inflammation in the gut and brain. Graphical abstract: Image, graphical abstract